Possibility of a New Indication for Amantadine in the Treatment of Bipolar Depression—Case Series Study - Marek Krzystanek; Artur Pałasz (Pharmaceuticals, 2020)
Bipolar disorder is a chronic and remitting mental illness. Antidepressants are not effective in treating acute bipolar depression, and antipsychotic drugs used in the treatment of bipolar depression cause frequent side effects. This situation justifies the search for new drugs as well as the repurposing of drugs used in other indications. In an open and naturalistic serious case study, 4 patients diagnosed with bipolar I disorder, chronically treated with a mood stabilizer, in whom at least two antidepressants were ineffective in the depressive phase, were treated with amantadine. The woman received 100 mg/day and 3 men received the target dose of 200 mg/day. All patients treated with amantadine improved their depressive symptoms after 1 week of treatment. None of them experienced side effects or manic switch. To reduce the risk of a manic switch, the treatment with amantadine was discontinued 2 weeks after the improvement of depressive symptoms, and no recurrence of depressive symptoms was observed. Amantadine may be a further therapeutic option for the treatment of acute bipolar depression. The drug in this indication may act quickly and be well tolerated. Confirmation of the antidepressant efficacy of amantadine in this indication requires replication of the results and conducting clinical trials.